D-4F Ameliorates Contrast Media–Induced Oxidative Injuries in Endothelial Cells via the AMPK/PKC Pathway - Guo, Yansong; Li, Wei; Qian, Mingming; Jiang, Ting; Guo, Ping; Du, Qian; Lin, Na; Xie, Xianwei; Wu, Zhiyong; Lin, Donghai; Liu, Donghui (Frontiers in Pharmacology, 2021)
Endothelial dysfunction is involved in the pathophysiological processes of contrast media (CM)-induced acute kidney injury (CI-AKI) after vascular angiography or intervention. Previous study found that apolipoprotein A-I (apoA-I) mimetic peptide, D-4F, alleviates endothelial impairments via upregulating heme oxygenase-1 (HO-1) expression and scavenging excessively generated reactive oxygen species (ROS). However, whether D-4F could ameliorate oxidative injuries in endothelial cells through suppressing ROS production remains unclear. In this study, a representative nonionic iodinated CM, iodixanol, was chosen for the in vitro and in vivo studies. Endothelial cell viability was assayed using micrographs, lactate dehydrogenase (LDH) activity and cell counting kit-8 (CCK-8). Apoptosis was detected using flow cytometry analysis and caspase-3 activation. Endothelial inflammation was tested using monocyte adhesion assay and adhesion molecule expression. ROS production was detected by measuring the formation of lipid peroxidation malondialdehyde (MDA) through the thiobarbituric acid reactive substances (TBARS) assay. Peroxynitrite (ONOO⁻) formation was tested using the 3-nitrotyrosine ELISA kit. Iodixanol impaired cell viability, promoted vascular cell adhesion molecule-1 (VCAM-1) and intercellular cell adhesion molecule-1 (ICAM-1) expression, and induced cell apoptosis in human umbilical vein endothelial cells (HUVECs). However, D-4F mitigated these injuries. Furthermore, iodixanol induced the phosphorylation of protein kinase C (PKC) beta II, p47, Rac1 and endothelial nitric-oxide synthase (eNOS) at Thr495, which elicited ROS release and ONOO⁻ generation. D-4F inhibited NADPH oxidase (NOX) activation, ROS production and ONOO⁻ formation via the AMP-activated protein kinase (AMPK)/PKC pathway. Additionally, after an intravascular injection of iodixanol in Sprague-Dawley rats, iodixanol induced a remarkable inflammatory response in arterial endothelial cells, although significant apoptosis and morphological changes were not observed. D-4F alleviated the vessel inflammation resulting from iodixanol in vivo. Collectively, besides scavenging ROS, D-4F could also suppress ROS production and ONOO⁻ formation through the AMPK/PKC pathway, which ameliorated oxidative injuries in endothelial cells. Hence, D-4F might serve as a potential agent in preventing CI-AKI.